STUDY OF PHYSICOCHEMICAL AND MICROBIOLOGICAL QUALITY OF THE SPRING WATERS OF THE REGION OF OUM TEBOUL WILAYA OF EL TARF- ALGERIA - SABRINA BOUCHELAGHEM; SAMIA MOUISSI; CHAIMA BENZERAA; ROUMAISSA KHALFOUN (Journal of Engineering Studies and Research)
The present work aims to assess the physico-chemical and microbiological parameters of the waters of the three sources (Ain Bergougaya, Ain Sigleb and Siporex) in the region of Oum el Teboul wilaya of El Tarf. Parameters such as temperature, pH, conductivity and salinity were measured in situ with a field multimeter. Hardness (62 mg/L to 266 mg/L), salinity (0.01 to 1 mg/L). From a microbiological point of view, there has been no evidence of the complete absence of germs of contamination such as total coliforms and fecal coliforms. This study compared to the drinking water standards shows that the waters in the area studied are of good quality.